DESIGN EMPLOYEE ATTENDANCE INFORMATION SYSTEM USING BARCODE CODE 39 - Suharjo, Suharjo; Sakban, Muhammad (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
The development of information and Communication Technology at this time has touched all sides of life. There is almost no side of human life that is not touched by information technology, not least also with computerization that is popular in the corporate environment. When in ancient times everything was still done manually. However, at this time all the leaders and management of the company have realized the importance of this information technology product that can facilitate them in carrying out Daily company functions. Many a design that uses computerized attendance but not integrated with attendance recording. Attendance recording is still manual so that it takes a long time in the process of making attendance because they have to do the counter manually. In this study will be designed a computerized attendance information system where the attendance process using database processing applications ysng assisted by using the barcode method code 39. The final result of the design of attendance information system is expected to help companies to manage attendance data effectively and efficiently.